Benchmarking In Disability Management At Tertiary Level - Parveen, Kaur; Arif, Jawaid (Publications International Lahore, Pakistan, 2019)
The purpose of this paper is to find the extent of Special Needs Students’ (SNS) awareness of disability provision in an institution because this lack of awareness is affecting their education drastically consequently, leading to frustration, de-motivation, and trauma. An empirical study was carried out in a private higher institution of Malaysia, by identifying ten SNS to be observed and subsequently they were interviewed. For reliability and validity of the data the literature review, observation, interviews, and content analysis were carried out to develop a framework to find the extent of the disability provision in an institution. This framework is a prelude to a comprehensive one in the future for the use of a variety of stakeholders including heads of tertiary institutions, NGOs involved in tertiary education, disability teachers and students with disabilities.